2011
DOI: 10.1130/b30392.1
|View full text |Cite
|
Sign up to set email alerts
|

Erosion, storage, and transport of sediment in two subbasins of the Rio Puerco, New Mexico

Abstract: Arroyos in the American Southwest proceed through cut-and-fi ll cycles that operate at centennial to millennial time scales. The geomorphic community has put much effort into understanding the causes of arroyo cutting in the late Quaternary and in the modern rec ord (late 1800s), while little effort has gone into understanding how arroyos fi ll and the sources of this fi ll. Here, we successfully develop a geographic information system (GIS)-modeled sediment budget that is based on detailed fi eld measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…Waves of incision may be followed by upstream propagating waves of deposition as a result of local widening and transport of sediment from incising reaches upstream (Schumm and Hadley, 1957;Gellis et al, 2012). Experimental studies have sometimes shown that the wave of deposition is followed by re-incision as the sediment source becomes more remote ("complex response" of Schumm and Parker, 1973).…”
Section: Arroyosmentioning
confidence: 95%
See 4 more Smart Citations
“…Waves of incision may be followed by upstream propagating waves of deposition as a result of local widening and transport of sediment from incising reaches upstream (Schumm and Hadley, 1957;Gellis et al, 2012). Experimental studies have sometimes shown that the wave of deposition is followed by re-incision as the sediment source becomes more remote ("complex response" of Schumm and Parker, 1973).…”
Section: Arroyosmentioning
confidence: 95%
“…Arroyos are deep, oversized channels usually with vertical or steeply cut walls of silt, clay, or sand (Dodge, 1902;Schumm and Hadley, 1957;Cooke and Reeves, 1976;Gellis et al, 2012). They occur in semiarid or arid regions worldwide (Prosser et al, 2001;Sancho et al, 2008;Mehl and Zárate, 2012;Boardman, 2014).…”
Section: Arroyosmentioning
confidence: 97%
See 3 more Smart Citations